High affinity IgM+ memory B cells are generated through a germinal center-dependent pathway. Issue 2 (December 2015) - Hara, Yasushi; Tashiro, Yasuyuki; Murakami, Akikazu; Nishimura, Miyuki; Shimizu, Takeyuki; Kubo, Masato; Burrows, Peter D.; Azuma, Takachika
Graphical abstract: Highlights: Germinal center reaction in spleen. Active induction of somatic hypermutation in IgM. Down-regulation of class-switch recombination. Abstract: During a T cell-dependent immune response, B cells undergo clonal expansion and selection and the induction of isotype switching and somatic hypermutation (SHM). Although somatically mutated IgM + memory B cells have been reported, it has not been established whether they are really high affinity B cells. We tracked (4-hydroxy-3-nitrophenyl) acetyl hapten-specific GC B cells from normal immunized mice based on affinity of their B cell receptor (BCR) and performed BCR sequence analysis. SHM was evident by day 7 postimmunization and increased with time, such that high affinity IgM + as well as IgG + memory B cells continued to be generated up to day 42. In contrast, class-switch recombination (CSR) was almost completed by day 7 and then the ratio of IgG1 + /IgM + GC B cells remained unchanged. Together these findings suggest that IgM + B cells undergo SHM in the GC to generate high affinity IgM + memory cells and that this process continues even after CSR is accomplished.